Heparin and dextran sulfate: their role on rsv infectivity - Rubio, Marcelo [UNESP]; Toledo, Karina Alves; Calça, Jaqueline [UNESP]; Bonfim, Caroline Measso [UNESP]; Gomes, Deriane Elias; Durigon, Edison Luiz; Fossey, Marcelo Andres; Rahal, Paula [UNESP]; Souza, Fátima Pereira de [UNESP] (My University, 2010)
Respiratory syncytial virus is the major cause of acute lower respiratory tract illness in infants and young children. Because there is currently no licensed vaccine for RSV, there is a substantial interest in the identification and development of RSV specific inhibitory agents. There are clinical evidences that glycosaminoglycans (GAGs) are potential inhibitors of viral infection. In this study, the performance of two GAGs (heparin and dextran sulfate) were compared for their antiviral and virucidal activities on RSV. Analysis was performed using an in vitro infection model where, previously to infection, Hep-2 cells or RSV were incubated with heparin or dextran sulfate. The presence of viral particles was analyzed by Reverse Transcriptase-Polimerase Chain Reaction (RT-PCR) and indirect immunofluorescence assays (IFA). The results showed that viral infection was more efficiently inhibited when Hep-2 cells were pre-incubated with heparin or, when viral particles were pre-incubated with dextran sulfate. Our study suggest that, in the absence of cellular death, heparin and dextran sulfate reduce RSV infection by different mechanisms, antiviral and virucidal ones, respectively. These data contribute for recent medical, microbiology and biochemical studies which suggest that the use of antiviral and virucidal compounds as more effective treatment to control virus infections.
Keywords: antiviral; virucidal; human syncytial respiratory virus; heparin; dextran; sulfate